An investigation of the perceptions of laboratory animal welfare issues among undergraduate and graduate veterinary students in southeastern China - Yan, Shihong; Li, Hongyang; Lin, Jin; Chen, Huimin; Liu, Shasha; Diao, Hongxiu (Frontiers in Veterinary Science, 2024)
Animal experiments have played a significant role in advancing scientific knowledge and enhancing the quality of life. In order to better understand the opinions and knowledge of veterinary students towards laboratory animal welfare and to explore and advance the teaching methods of animal ethics education, a self-made questionnaire was designed to conduct a survey among undergraduate and postgraduate veterinary majors. The investigation content encompassed various aspects, such as the students' level of knowledge on animal welfare, their perspectives on laboratory animals, their proficiency in animal experiments, and their opinions on teaching methods and contents. The survey had a total of 150 undergraduate students and 148 graduate students as respondents. The survey results indicate that most students have a strong sense of responsibility towards safeguarding the welfare of experimental animals. However, there are a few students who lack compassion for animals. Additionally, there is a general lack of basic theoretical knowledge of animal ethics and an inadequate grasp of experimental techniques among current students. Furthermore, most of the participants expressed a strong sense of responsibility toward animal welfare advocacy. Although a substantial number of students are unaware of the existence of laboratory animal welfare supervision agencies, they support teaching and supervision actions related to animal welfare and are open to different teaching methods and content. In conclusion, targeted training and education regarding laboratory animal welfare and ethics should be conducted in the future to address the specific needs of students. This study provides the foundation for future animal welfare education and will help improve the professional skills and humanistic qualities of veterinary students.